Deciphering the growth pattern and phytohormonal content in Saskatoon berry (Amelanchier alnifolia) in response to in vitro cytokinin application - Moyo, Mack; Aremu, Adeyemi O; Plačková, Lenka; Plíhalová, Lucie; Pěnčík, Aleš; Novák, Ondřej; Holub, Jan; Doležal, Karel; Staden, Johannes Van (New biotechnology, 2018)
Clonal propagation plays a critical integral role in the growth and success of a global multi-billion dollar horticulture industry through a constant supply of healthy stock plants. The supply chain depends on continuously improving the micropropagation process, thus, understanding the physiology of in vitro plants remains a core component. We evaluated the influence of exogenously applied cytokinins (CKs, N6-benzyladenine = BA, isopentenyladenine = iP, meta-topolin = mT, 6-(3-hydroxybenzylamino)-9-(tetrahydropyran-2-yl)purine = mTTHP) in Murashige and Skoog (MS)-supplemented media on organogenic response and accumulation of endogenous CK and indole-3-acetic acid (IAA) metabolites. The highest shoot proliferation (30 shoots/explant) was obtained with 20 μM mT treatment. However, the best quality regenerants were produced in 10 μM mT treatment. Rooting of Amelanchier alnifolia in vitro plantlets was observed at the lowest CK concentrations, with the highest root proliferation (3 roots/explant) in 1 μM mTTHP regenerants. Similar to the organogenic response, high levels of endogenous bioactive CK metabolites (free bases, ribosides, and nucleotides) were detected in mT and mTTHP-derived regenerants. The level of O-glucosides was also comparatively high in these cultures. All CK-treated plants had high levels of endogenous free IAA compared to the control. This may suggest an influence of CKs on biosynthesis of IAA.
Keywords: Organogenesis; ovoce; Cytokinins; Topolins; Fruit; Micropropagation; Auxins; Saskatoon berry; Rosaceae; Endogenous cytokinins; cytokininy